2019
DOI: 10.2174/1574887113666181102111247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chondroitin Sulfate on Blood Serum Cytokine Profile during Carrageenan-induced Edema and Monoiodoacetate-induced Osteoarthritis in Rats

Abstract: Background: Blood cytokines affect the development of inflammatory processes in both normal and pathological states. We have studied changes in the concentration of interleukins (ILs) - 1β, IL-4, IL-10, IL-12B p40, transforming growth factor β (TGF β), tumor necrosis factor (TNF-α) in acute carrageenan-induced inflammation and degenerative-dystrophic changes of knee joint caused by monoiodoacetate-induced Osteoarthritis (OA) in experimental models on rats. We also investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Despite an increase in the level of TGFbeta in MIA-OA that correlates with an increased expression of the TGF-β gene in cartilage [57], our other study showed negative histological changes [19]. This may indicate insufficient compensatory effort against a significant increase of pro-inflammatory cytokines in the cartilage and blood [58], and may also be associated with fibrosis and cartilage degeneration [59].…”
Section: Resultsmentioning
confidence: 78%
“…Despite an increase in the level of TGFbeta in MIA-OA that correlates with an increased expression of the TGF-β gene in cartilage [57], our other study showed negative histological changes [19]. This may indicate insufficient compensatory effort against a significant increase of pro-inflammatory cytokines in the cartilage and blood [58], and may also be associated with fibrosis and cartilage degeneration [59].…”
Section: Resultsmentioning
confidence: 78%
“…GT activity decreased in 1.6 times in blood serum of rats with MIA-OA, compared to control group (Table 3). Decreasing of GT activity may be a response to an excess of toxic oxygen metabolites, due to the development of the inflammatory process [26,49]. GT is highly specific to reduced glutathione, and a decrease in GSH pool can cause a decrease in enzyme activity [50].…”
Section: Resultsmentioning
confidence: 99%
“…Induction of monoiodoacetate (MIA) into the patellofemoral joint of an experimental rat model induces histopathological changes in the knee joint that similar to those during tibiofemoral OA [23]. MIA-induced model of OA (MIA-OA) in rats is widely used to describe morphology, loss of mobility and biochemistry of the disease [24,25], significant changes of cytokine profile [26].…”
mentioning
confidence: 99%
“…
damage to the liver and the intestine can result from the side effects of drugs such as: nonsteroidal anti-inflammatory glucocorticoids, salazopyrazins, statins, antihypertensives, proton pump inhibitors etc. [13][14][15][16][17].The practical importance of this paper consists in clarifying the mechanisms of progression of steatohepatitis and chronic colitis, improving the efficacy of this pathology treatment with the use of a modern nano-hepatoprotector. While there are data on treatment of hepatic and/or intestinal diseases [6], this paper emphasizes treatment of patients with steatohepatitis and concomitant chronic colitis.The study objective is evaluation of the treatment efficacy of steatohepatitis with concomitant chronic colitis using phosphatidylcholine and glycyrrhizic acid.
MATERIALS AND METHODSEighty-seven patients with steatohepatitis in combination with chronic colitis were examined in the gastroenterology day hospital of the advisory diagnostic center in Podolsk district of the city of Kiev, including those with non-alcoholic steatohepatitis (NASH) -38 (44%), alcoholic steatohepatitis (ASH) -28 (32%), drug-induced liver injury (DILI) -21 (24%).
…”
mentioning
confidence: 99%
“…damage to the liver and the intestine can result from the side effects of drugs such as: nonsteroidal anti-inflammatory glucocorticoids, salazopyrazins, statins, antihypertensives, proton pump inhibitors etc. [13][14][15][16][17].…”
mentioning
confidence: 99%